The Effects of Acceptance and Commitment Therapy (ACT) on Depression in TB-HIV Co-infection Patients - Avin Maria; Untung Sujianto; Niken Safitri Dyan Kusumaningrum (Universitas Airlangga, 2020)
Introduction: The most common psychological problem in TB-HIV coinfection patients is depression. Acceptance and Commitment Therapy (ACT) is an intervention that encourages participants to change their relationships with their thoughts and physical sensations through mechanisms of acceptance and value-based action. This present study has been carried out to investigate the effectiveness of ACT in treating TB-HIV coinfection patients.Methods: This research was a quasi-experiment. This study involved 62 respondents diagnosed TB-HIV coinfection by doctor, experienced mild depression to severe depression, able to communicate well and have not hearing loss. ACT was given by a researcher with six sessions) one session per day) held in the intervention group. Data were collected using Beck Depression Inventory (BDI) questionnaires. Data analysis use paired t-test to determine the differences in value of depression on pre-test and post-test in each group. Data were analyzed using the independent t-test to determine the effect of ACT on depression.Results: The majority of respondents were male (66.1%). Most of the early adult and older adult respondents had moderate depression, while middle-aged adult mostly had severe depression (50%). The fully unemployed respondents had severe depression (100%). The analysis results showed that there was a more significant decrease in depression in the intervention group given ACT compared to the control group (p value =0.00).Conclusion: ACT has an effect on reduce depression of TB-HIV coinfection patients. ACT is recommended to be developed as a nursing intervention that can be given to patients who are depressed.